2019
DOI: 10.21205/deufmd.2019216327
|View full text |Cite
|
Sign up to set email alerts
|

Sığacık Körfezi ve Doğanbey Burnu Deniz İçi Termal Su Kaynaklarının Deniz Suyuna Kimyasal ve Fiziksel Etkileri (Sonbahar 2016-İlkbahar 2017)

Abstract: 2 ) de analiz edilmiş olup; dip suların kimyasal özelliklerinin deniz suyu/yüzey suyu ile benzer özellikte olduğu belirlenmiştir. Bununla birlikte Nisan 2017 yılında altı istasyonda su kolonu içerisindeki sıcaklık, tuzluluk, iletkenlik ve yoğunluğun değişimi CTD cihazı ile ölçülmüştür. CTD verilerine göre dip su sıcaklığı C1 (87m) -16,64°C, C2 (21,8m) -16,79°C, C3 (36,5m) -16,70°C, C4 (27,8m) -16,72°C, C5 (51m) -17,16°C ve C6 (51m) -16,51°C ölçülmüştür. İstasyonlardaki sıcaklık profillerini karşılaştırdığımızd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In their study, the deep water samples were analyzed and the concentrations of Ca + , Mg + ², Na + ², K + , Li + , As, B + , Clˉ, SO 4ˉ³ , SO 2 , and HCOˉ³, and the temperature, salinity, conductivity, and density values were measured. Bakak and Özel (2019) reported that there were no chemical effects on the seawater of the submarine thermal springs; on the other hand, the temperature values of the deep water samples were higher in the stations near Doğanbey Cape.…”
Section: Study Areamentioning
confidence: 96%
See 2 more Smart Citations
“…In their study, the deep water samples were analyzed and the concentrations of Ca + , Mg + ², Na + ², K + , Li + , As, B + , Clˉ, SO 4ˉ³ , SO 2 , and HCOˉ³, and the temperature, salinity, conductivity, and density values were measured. Bakak and Özel (2019) reported that there were no chemical effects on the seawater of the submarine thermal springs; on the other hand, the temperature values of the deep water samples were higher in the stations near Doğanbey Cape.…”
Section: Study Areamentioning
confidence: 96%
“…In addition, Sığacık Bay experienced significant serious earthquakes on 17 to 20 October, 2005; therefore, the region has been a center of interest by many researchers (Gürçay et al, 2007;Ocakoğlu et al, 2004;Benetatos et al, 2006;Aktar et al, 2007;Sözbilir et al, 2009;Gürçay, 2014;Bakak et al, 2015;Yolsal-Çevikbilen et al, 2014;Bakak, 2017). The chemical (Ca + , Mg + ², Na +2 , K + , Li + , As, B + , Clˉ, SO 4ˉ³ , SiO 2 , and HCOˉ³) and physical (temperature, salinity, conductivity, and density) effects to seawater of the submarine thermal springs in Sığacık Bay and Doğanbey Cape were evaluated by Bakak and Özel (2019). In their study, the deep water samples were analyzed and the concentrations of Ca + , Mg + ², Na + ², K + , Li + , As, B + , Clˉ, SO 4ˉ³ , SO 2 , and HCOˉ³, and the temperature, salinity, conductivity, and density values were measured.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation